2015
DOI: 10.30935/cedtech/6157
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Online Mathematics Teaching with Pen-based Technology: Experiences of Two Instructors

Abstract: The purpose of this study was to explore instructors' perspectives on the effect of using pen-based technology in the online mathematics courses and understand instructors' experiences in online mathematics teaching with pen-based technology. In this study, two instructors who taught online mathematics courses in fourteen weeks used digital pen as a pen-based technology. The data were obtained from semi-structured interviews and observation of online mathematics course records. The findings indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Animated figures and mathematical representations were found beneficial for improving students’ mathematical understanding and solving mathematical problems (Voskoglou, 2019 ). With the help of tablets with freehand writing tools and authoring tools/apps that permit online sharing, mathematical concepts, symbols, and solution process steps can now be communicated easily in online mathematical courses, positively impacting interaction and students’ participation in online mathematical courses (Karal et al, 2015 ). This technology has also been beneficial in changing some of the lectures’ negative attitudes towards online mathematics courses.…”
Section: Teaching and Learning Of Mathematics In Online Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animated figures and mathematical representations were found beneficial for improving students’ mathematical understanding and solving mathematical problems (Voskoglou, 2019 ). With the help of tablets with freehand writing tools and authoring tools/apps that permit online sharing, mathematical concepts, symbols, and solution process steps can now be communicated easily in online mathematical courses, positively impacting interaction and students’ participation in online mathematical courses (Karal et al, 2015 ). This technology has also been beneficial in changing some of the lectures’ negative attitudes towards online mathematics courses.…”
Section: Teaching and Learning Of Mathematics In Online Settingsmentioning
confidence: 99%
“…This technology has also been beneficial in changing some of the lectures’ negative attitudes towards online mathematics courses. They felt more comfortable teaching mathematics in online environments after using this technology (Karal et al, 2015 ).…”
Section: Teaching and Learning Of Mathematics In Online Settingsmentioning
confidence: 99%
“…First, this study shows that the website is a learning media to support elearning; several previous studies have also shown that the website is a learning media that is often used in e-learning (Astuti et al, 2020;Dogan & Dikbıyık, 2016;Hamdunah et al, 2016;Lestari, 2019;Usta, 2011), however teachers still have difficulty applying math concepts on the website. This is because teaching math concepts is very difficult for teachers (Indriani et al, 2018;Maulydia et al, 2017), and also added to the factor of teachers who still have difficulty teaching online (Karal et al, 2015;Kebritchi et al, 2017;Wang & Ip, 2010). Many teachers have understood the selection of alternative media during the pandemic, including using Learning Management Systems (LMS) (eg Google Classroom and Edmodo) as well as facilities such as video conference (eg Zoom and Google Meet).…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent studies have indicated that mathematics teaching practices in the OLE differ from the traditional classroom (face-to-face lectures) and that technological-pedagogical competencies shape applications in mathematics classes (Arcavi, 2020 ; Bennison et al, 2020 ; Borba et al, 2018 ). With the help of tablets with flexible writing tools that allow online sharing (Karal et al, 2015 ), and with the support of web 2.0 tools designed particularly for mathematical learning areas (such as dynamic geometry software and online data analysis platforms), mathematical concepts, symbols and solution process steps can now be easily presented to students interactively in the OLE. Arcavi ( 2020 ) also pointed out that digital tools used in mathematics education increase the capabilities of teachers to access and manage teaching content.…”
Section: Conceptual Frameworkmentioning
confidence: 99%